Job mobility and the gender wage gap in Italy - Del Bono, Emilia; Vuri, Daniela (Munich, 2008)
"This paper investigates the way in which job mobility contributes to the emergence of a gender wage gap in the Italian labour market. We show that men experience higher wage growth than women during the first 10 years of their career, and that this difference is particularly large when workers move across firms. This gender mobility penalty is robust to the inclusion of individual, job and firm characteristics, to different ways of accounting for individual unobserved heterogeneity, and is mainly found for voluntary job moves. Exploring the wage growth of job movers, we find that a significant gender wage penalty emerges when workers move to larger firms. This might be explained by the fact that bigger establishments offer jobs more highly valued by women than men or that the relationship between job satisfaction and firm size is less negative for women than men. Using data on job satisfaction, we find evidence for the latter hypothesis as well as some indication that wages and fringe benefits compensate for lower levels of job satisfaction in larger firms, but that this is so only for men. "